Measuring and mapping the existence of phantom borders at a local scale: example of Sudetenland in Czechia - Pavlína Netrdová; Matěj Korčák; Vojtěch Nosek (Journal of Maps)
This study presents an innovative methodological approach for quantitatively measuring and mapping the existence of phantom borders. Phantom borders are former political borders that have not existed for decades, but their presence is still visible in current socio-geographical differentiation. The visualisations based on spatial statistical analysis of territorially detailed data enables revealing and assessing potential heterogeneous border effects at a local scale. The approach is demonstrated on an example of a phantom border of Sudetenland in Czechia using data for two different phenomena of demographical and social nature. Given the detailed local data, the presented maps assist with interpretation and analytical conclusions. Two main maps show the effect size of the phantom border and its variability in space and time. Four additional maps visualise the results of hot spot analysis and their relationship to the phantom border.